Breast and cervical cancer: the problem of the lack of preventive actions in women - Rodríguez-Garcés, Carlos René; Padilla-Fuentes, Geraldo Bladimir (Universidad y Salud, 2019)
Introduction: The prevalence of cancer is a problem that goes beyond medical concern since it involves subjective and social aspects that affect the lives of those who either suffer from cancer or are at risk for it. Therefore, it is important to detect it early, especially among women due to their exposure to risk factors for breast and cervical cancer. Objective: To analyze women’s abstention from mammography and Papanicolaou screening in Chile. Materials and methods: A multivariate binomial logistic regression analysis was conducted with available data from the Health Module of the National Socioeconomic Characterization Survey (NSCS) from 2015. Results: Even though there is a high prevalence of both types of cancer, there is a generalized female abstention from preventive actions. Personal reasons are the most common justifications given for avoidance of mammography and/or Papanicolaou test, especially undervaluing their importance. Factors that increase the probability of abstention include low education level, lack of medical affiliation, and presence of a partner. Conclusions: It is important to increase the coverage of preventive services, focus resources towards vulnerable populations, and create incentive strategies for women to take these exams.